Tooth agenesis: An overview of diagnosis, aetiology and management - Maurice J. Meade; Craig W. Dreyer (Elsevier, 2023)
Patients with one or more developmentally absent teeth are routinely encountered in dental practice. Tooth agenesis can be associated with significant functional, aesthetic and psycho-social problems. The present article provides an overview of the prevalence and aetiology of tooth agenesis, as well as the condition's clinical characteristics and management options with reference to the evidence base. A timely diagnosis can facilitate the appropriate planning and management which might not be straightforward, and patient care will likely require multi- and inter-disciplinary input. It is critical that dental care practitioners are aware of the clinical characteristics and management options for tooth agenesis.